2014
DOI: 10.1371/journal.pone.0088024
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Regulates Rat Male Germ Cell Function through Reactive Oxygen Species

Abstract: Besides giving structural support, Sertoli cells regulate the fate of germ cells by supplying a variety of factors. These factors include hormones, several pro- and anti-apoptotic agents and also energetic substrates. Lactate is one of the compounds produced by Sertoli cells, which is utilized as an energetic substrate by germ cells, particularly spermatocytes and spermatids. Beyond its function as an energy source, some studies have proposed a role of lactate in the regulation of gene expression not strictly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…Testicular cells were isolated as described previously by Galardo et al [26] with minor modifications. Germ cells were isolated from testes of 6 rats aged 21d in each experiment.…”
Section: Germ-cell Isolationmentioning
confidence: 99%
“…Testicular cells were isolated as described previously by Galardo et al [26] with minor modifications. Germ cells were isolated from testes of 6 rats aged 21d in each experiment.…”
Section: Germ-cell Isolationmentioning
confidence: 99%
“…Nevertheless, lactate production by Sertoli cells adluminal compartment. There is evidence that lactate has a crucial role in spermatogenesis (7,11) and also exhibits an anti-apoptotic effect on germ cells (8). Sertoli cells represent one of the predominant sources of lactate in the seminiferous tubules.…”
Section: Resultsmentioning
confidence: 99%
“…In testis, lactate also plays other key roles more than just serves as a substrate in metabolism. Previous reports showed that the lactate, which exerted an anti-apoptotic effect on germ cells40, was responsible for RNA and protein synthesis and improved spermatogenesis41. However, the elucidation of how lactate exerts its role in spermatocytes exactly is still very limited.…”
Section: Discussionmentioning
confidence: 99%